2013
DOI: 10.1016/j.agrformet.2013.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugarcane harvest method on microclimate in Florida and Costa Rica

Abstract: 2016-12-23T18:49:38

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
1
16
0
3
Order By: Relevance
“…The presence of the sugarcane straw blanket on the soil surface was expected to suppress plant tillering by lowering soil temperatures (Viator et al, 2005; Toppa et al, 2010; Sandhu et al, 2013; Awe et al, 2015; Correa et al, 2017) and acting as a physical barrier to tillering. Previous studies, however, have shown variable plant tillering responses to straw cover.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the sugarcane straw blanket on the soil surface was expected to suppress plant tillering by lowering soil temperatures (Viator et al, 2005; Toppa et al, 2010; Sandhu et al, 2013; Awe et al, 2015; Correa et al, 2017) and acting as a physical barrier to tillering. Previous studies, however, have shown variable plant tillering responses to straw cover.…”
Section: Resultsmentioning
confidence: 99%
“…Reducing incident light delays sprouting of basal vegetative buds (Toppa et al, 2010). Reducing soil temperature during the winter (Sandhu et al, 2013) and increasing soil moisture in early spring can limit plant growth and reduce stalk yield (Kingston et al, 2005; Viator et al, 2005; Viator and Wang, 2011). Sandhu et al (2017) reported negative effects of a straw blanket on plant tillering and leaf area index (LAI) from 120 to 200 d but no effect on final stalk yield and sucrose concentrations under subtropical conditions.…”
mentioning
confidence: 99%
“…Sugarcane cultivation has caused enormous changes in land use with the removal of tropical forest and other vegetation types (Scherr and Sthapit 2009). Some practices related to sugarcane such as burning bring with them the further decline of air and soil quality and affect the regional climate due to variations of soil temperature (Sandhu et al 2013), which can be reflected for example in the heat flux and moisture transport at this scale. The common practice of sugarcane burning methods, before and after the harvest, is an anthropogenic source of emissions of greenhouse gases (GHG) and aerosol to the atmosphere that may also cause respiratory toxicity (França et al 2012, Mazzoli-Rocha et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…A decomposição desse material resulta na ciclagem dos nutrientes VITTI, 2012), no maior tamanho de agregados (ROSSETTI et al, 2014), porosidade total e redução da densidade (DANTAS et al, 2010), maior umidade do solo e menor resistência à penetração (ROSIM et al, 2012). A presença da palha também está associada a redução na infestação de plantas daninhas (MARTINS et al, 1999), menor perda de água por evaporação (PERES; SOUZA; LAVORENTI, 2010) e dissipação de radiação solar excedente (SANDHU et al, 2013).…”
Section: Introductionunclassified